2011
DOI: 10.1080/09603123.2011.560252
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone levels in female workers exposed to urban pollutants

Abstract: The aim of this study was to evaluate if there were alterations in FSH plasma levels in female outdoor workers (traffic policewomen and drivers) exposed to chemical urban stressors vs. control group. After excluding subjects with main confounding factors, traffic policewomen, drivers and indoor workers were matched by age, working life, socioeconomic status, marital status, menstrual cycle day, age of menarche, habitual consumption of Italian coffee and soy. A total of 129 female subjects were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In male traffic policemen, lower free testosterone (Sancini et al, 2011) and higher luteinizing hormone (Tomao et al, 2009) and follicle-stimulating hormone (Tomei et al, 2009) plasma levels were reported. Studies on female traffic police observed significantly higher plasma free testosterone (Tomei et al, 2008) and follicle-stimulating hormone levels during the proliferative phase of the menstrual cycle (Ciarrocca et al, 2011). …”
Section: The Role Of Source Typesmentioning
confidence: 99%
“…In male traffic policemen, lower free testosterone (Sancini et al, 2011) and higher luteinizing hormone (Tomao et al, 2009) and follicle-stimulating hormone (Tomei et al, 2009) plasma levels were reported. Studies on female traffic police observed significantly higher plasma free testosterone (Tomei et al, 2008) and follicle-stimulating hormone levels during the proliferative phase of the menstrual cycle (Ciarrocca et al, 2011). …”
Section: The Role Of Source Typesmentioning
confidence: 99%
“…In fact, an increasing number of studies suggest that chemicals and pollutants in the environment, such as those arising from the traffic which are caused and spread by human activities, can affect the male reproductive system [106,107,108,109,110,111,112,113,114,115,116] and act as an endocrine disruptor because of their adverse effects on reproduction [117,118] and disruption of steroidogenesis and spermatogenesis [119,120]. Nickel pollution, taken as water-soluble, sulfidic, oxidic or metallic form, is known to modify the function of proteins in mammalian testes in terms of fertility and/or hormone production [119].…”
Section: Discussionmentioning
confidence: 99%
“…In male traffic policemen, lower free testosterone (Sancini et al, 2011) and higher luteinizing hormone (Tomao et al, 2009) and follicle-stimulating hormone (Tomei et al, 2009) plasma levels were reported. Studies on female traffic police observed significantly higher plasma free testosterone (Tomei et al, 2008) and follicle-stimulating hormone levels during the proliferative phase of the menstrual cycle (Ciarrocca et al, 2011).…”
Section: Rationalementioning
confidence: 99%